PENDIDIKAN KARAKTER PADA CERITA BHAGAWAN DOMYA - I Made Suweta (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2018)
Character values when associated with the teachings of Hinduism contain a lot ofeducation about ethics, morals and character. Such a system or method of education can beseen, among others, in the story of Adi Parwa who is one of the subItihasain the Mahabarataepic, one of which tells how the teachings of a teacher named Bhagawan Dhomya in educatingstudents or students, namely Sang Arunika, the Sang Utamanyu, and the Sang Weda. The writingmethod in question is related to data discovery and data analysis. In the discovery of the data,the literature study method is used, which is done by searching the literature which contains theBhagawan Domya story. Especially on the story of Adiparwa, there is a part that is fascinatingabout the Bahagwan Domya story. Through this literature study, a narrative of a story aboutBhagawan Domya was obtained, which then made a short story in the form of a story synopsis.Based on this search also found the story settings that include the setting of the time and placewhere the story occurred. Also through this literature search, the character and character inBhagawan Domya story are obtained. Based on the studies conducted, in this study found thethirteen values of character education reflected in the story which tells the students (SangArunika, Sang Utamanyu, and Sang Weda) who diligently carry out the task given by the teacher(Bhagawan Dhomya). the thirteenth character education is as follows: religious, honest, tolerance,discipline, hard work, creative, independent, democratic, love the country, respect achievement,care for the environment, social care, and responsibility.Keywords: Character Value, Adiparwa, Bhagawan Domya